Microbiological quality of the packaged chicken eggs within and after shelf life - Ahmad, Munirah (Pusat Pengajian Kesihatan, 2015)
Eggs are healthy and nutritious food which are commonly consumed everywhere in the world. However issues of its safety for consumption and other uses remain doubtful since food poisoning associated to eggs and its products . This study was undertaken to provide information on the effect of storage time that is within shelf life and after the expiry date on the microbiological quality of the egg by detecting the presence of bacteria especially E.coli and Salmonella spp. 30 egg samples randomly collected from selected supermarket in Kubang Kerian, Kelantan. The result showed presence of fecal coliform (£. coli) but no Salmonella was isolated from the samples. E. coli is present in both the eggshell and egg content sample. More egg samples in the expiry category showed presence of E. coli. Additionally, eight egg microflora (Citrobacter freundii, Enterobacter aerogenes, E. coli, Klebsiella pneumonia, Proteus mirabilis, Proteus vulgaris, Serratia marcesens and Shigella spp.) were isolated from the samples. . It is ix concluded that eggs passed the expiry date are not safe for consumption.